Análise qualitativa na utilização de indicadores de falta para a rede de distribuição - Stasiak, Josias Eduardo (2019)
The progressive evolution of electrical energy demand, interchained with increasingly digital lifes, require continuous improvements in the distribution system, rising its confiability, security, economics and service quality. By this mean, exploring electronic and digital resources that helps building those enhancements is essential. Fault Indicators are devices that may be an alternative to upgrade the current state, by monitoring and transmitting data about the distribution system. Therefore, appropriate actions and people’s logistics can be applied, avoiding superfluous energy usage as well as excessive time taken by the maintenance teams. A qualitative case study including these instruments will be analysed, considering the real economic resolutions for the power distribution company and consumers, as in related parameters to maintenance and restoration, like DEC (Equivalent duration of interruption by consumer unit). Five different cases are developed in a network test with the application of fault indicators and distributed generation (GD). The comparison among all cases results in clear viability for the project, then the estimated payback is seven faults or four months for the analysed network.